Penerapan Perikatan Dengan Ancaman Hukuman Dalam Perjanjian Endorse - Hardian Iskandar (Universitas Muhammadiyah Gresik, 2020)
This study aims to increase the understanding of the law regarding crowded agreements that are now used by the public, namely endorce agreements that are used in various types of social media. In the agreement used by regulations in Indonesia there is an agreement that is permitted or not by regulations so that the existence of this research can open insight into endorce agreements. Engagement with the threat of punishment alone reviews the existence of losses suffered by both the giver and the recipient in the agreement. Endorse itself is a marketing marketing for a product that is currently trending so that it is necessary to provide an understanding of regulation in civil law that applies both to endorsers and recipients of endorses agreed upon with an agreement.